Hubungan Sosial Ekonomi dan Pengetahuan dengan Status Gizi Ibu hamil - Almujahidiani, Titik; Rini Mayasari (STIKes Budi Mulia Sriwijaya, 2025)
A B S T R A C T The nutritional status of pregnant women is a measure of success in meeting the nutritional needs of pregnant women. Nutritional status affects the growth and development of the fetus, if the nutritional status is normal it is likely to give birth to a healthy baby. This study aims to determine the relationship between socio-economic and knowledge with the nutritional status of pregnant women. This study is a study using an analytical survey method with a cross-sectional approach. The sample of this study amounted to 45 respondents. Sampling in this study used the accidental sampling technique. sampling with chi square statistical test analysis with a significance level of α (0.05). The results of this study obtained mothers who had sufficient socio-economic knowledge with good nutrition as many as 20 respondents (55.6%) while sufficient knowledge with good nutrition as many as 20 respondents (57.1%). Based on the Chi Square test, the pa value was obtained at 0.03 and 0.04, so it can be concluded that there is a relationship between socio-economic and knowledge with the nutritional status of pregnant women at the Cambai Health Center.